A NEW WAY TO SOLVE BASIC EDUCATION PROBLEMS IN INDONESIA IN ADAPTING TO MULTICULTURALISM - Yuyun Elizabeth Patras; Rais Hidayat; Edwita Edwita; Zulela M. S.; Gusti Yarmi (UNIVERSITAS PAKUAN, 2022)
This study has the aim of describing the results of research on multiculturalism in Indonesia. The findings of the research papers will be used as the basis for finding new ways, especially for the implementation of multicultural education in the context of basic education that can be used to solve problems in education. The research method used a content analysis of 12 articles in English from 2018-2022 using the keyword